Structural properties of porous silicon/SnO2:F heterostructures - Garces Pineda, Felipe Andres (2012)
In this work we present structural studies made on SnO2 deposited on macroporous silicon structures. The porous silicon substrates were prepared by anodization of p-type silicon wafers. The SnO2 doped layers were synthesized by the sol?gel method from SnCl4·5H2O-ethanolic precursor, where the effect of fluorine doping level on structural properties was investigated. The fundamental structural parameters of tin oxide such as the lattice parameter and the crystallite size were studied in correlation with the dopant concentration. In addition, the effect of fluorine incorporation into the structure of tin oxide was analyzed on the basis of theoretical calculations that take into account the structural factor. The results obtained indicate that incorporation of fluorine occurs only at substitutional sites for SnO2 deposited on porous silicon.